On farm and off-farm feed utilization and improved management options: A Synthesis - Makkar, Harinder; Wamatu, Jane; Jones, Chris; Duncan, Alan; Louhaichi, Mounir; Varijakshapanicker, Padmakumar; Rudiger, Udo; Derseh, Melkamu; Ghimire, Sita; Lukuyu, Ben; Amole, Tunde (International Livestock Research Institute, 2022)
The challenges identified in the proposal of the CGIAR Research Program (CRP) on Livestock, for enhancing livestock production and productivity, have been the shortage of quality feeds, inefficient utilization of feed resources, degradation of rangelands, and lack of knowledge and skills of stakeholders in the feed production and utilization value chains. To address these challenges, the research and development work, innovations developed and tested, results-dissemination and concerted efforts towards capacity building have been presented in the following three main sections. 1) Enlarging the feed quality resource base 2) Efficient use of feed resources 3) Rehabilitation of degraded rangelands